Design of the Gear Shaping Process of Gear Pump Linear Conjugate Inner Tooth - Zhou Qinghua; Yang Zhongsheng; Deng Yingcheng (Jixie chuandong)
The processing technology of the special Linear conjugate internal gear shaping of gear pump is studied,and the gear shaper parameters which affects the machining accuracy of internal gear is obtained,on this basis,the relieving amount,column oblique movement,the gear tooth profile angle etc are analyzed and test.The results show that with the increase of the main movement speed and the workbench rotational speed,the inner gear processing interference is reduced,the cutting force and the workpiece cutting residual heat is decreased,the workpiece thermal deformation is become smaller,at the same time,the processing quality of workpiece surface is improved.